Cartografia das moradias em Canudos: a dimensão política do morar - Marques, Ana Carolina de Oliveira (2017)
The housing synthesizes a set of oppressions and appropriations constituents of the planned daily life that ensures the existence of a "bureaucratic society of directed consumption" (LEFEBVRE, 1991). Made of technical artifacts connected to the market, such as cement, brick, household items, passing through the mass culture that tends to infiltrate it’s visible or invisible pores, but open to a new mobility of symbols, of relationships that tend to strengthen the ties of solidarity, of sharing, in a kind of tension between the intimate and the world, between the fulfillment of daily living and friction with the global social structures of a mode of accumulation, housing forges itself in open tension and fertile, which we call existential cartographies. Based on concrete social experiences in the Canudos settlements (Palmeiras de Goiás - GO), the tensions that assaulted these territories, and the social movements in contemporary times, as well as the possibilities and gaps of this modern housing project were mapped. The political dimension of housing, which makes this act an instance of composition of the subject and of social action, the thesis defended in this work, demands a close look of the subjects and social movements to this space practice whose constraints and implications extrapolate the physical limits of the building: Living is a political and existential project. In living the subject composes relationships, makes choices, expresses worldviews, builds and fulfill not only the architectural object, but systems of references and values as well. Studies from different fields of knowledge besides Geography, such as architecture (ROLNIK, 2015), psychoanalysis (GUATTARI & ROLNIK, 1996) and anthropology (BRANDÃO, 2009) contributed to the composition of this work. In the face of widespread malaise, announced by educators, psychologists, psychoanalysts, anthropologists, sociologists among other social scientists, it is questionable: is it possible in this society to build good domestic relations? Field trips to the Canudos settlement, interviews with intellectuals, settlers and leaders of social movements, preparation of cartographic material, readings, debates, various expositions of the partial results (lectures, workshops, presentation of work in event) of the reflections launched in this work were procedures adopted to unveil the political dimension of housing and the limits and challenges posed to social movements in contemporary times.